Potensi Ekstrak Bunga Telang (Clitoria ternatea) Sebagai Pencegah Acute Kidney Injury (AKI) - Ersalita Rahmadhani Pratiwi; Sukma Oktavia Aulia Rahmandani; Achmad Rivaldy Ibrahim; Isbandiyah Isbandiyah (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2020)
Introduction: Butterfly pea (Clitoria ternatea) is a vine that has various colors such as pink, light blue, white, and purple. This plant is commonly used as a food coloring and ornamental plants. Butterfly pea has pharmacological potential, among others, as high antioxidants. The antioxidants of the butterfly pea show much higher activity than other flowers. Antioxidants are substances that can prevent the occurrence of Acute Kidney Injury (AKI), which is currently increasing in incidence and mortality due to AKI reaching 23.9% in adults and 13.8% in children. Aim of study: This article aims to discuss the potential of butterfly pea extract (Clitoria ternatea) as a preventative for Acute Kidney Injury (AKI). Method: The research method used is the literature search technique on 20 articles from the Google Scholar database. Results and Discussion: The results of the literature search show that the butterfly pea (Clitoria ternatea) has antioxidant compounds that have the potential to prevent the occurrence of acute kidney injury (AKI). Butterfly pea extract has the potential to reduce levels of urea, serum creatinine, reduce levels of malondialdehyde (MDA) and increase levels of glutathione, catalase, and superoxide dismutase (SOD). The antioxidant activity of flavonoids and tannins in butterfly pea extract was found to have a nephroprotective effect against exposure to toxic substances. Conclusion: The conclusion from this literature search is that the antioxidant content contained in butterfly pea extract can be a good alternative as a nephroprotector to prevent AKI.